Tantalum and magnesium nanoparticles enhance the biomimetic properties and osteo-angiogenic effects of PCL membranes - Nan, Jiangyu; Liu, Wenbin; Zhang, Kai; Sun, Yan; Hu, Yihe; Lei, Pengfei (Frontiers in Bioengineering and Biotechnology, 2022)
Segmental bone defects, accompanied by periosteum stripping or injuring, usually lead to delayed bone union or nonunion, which has always been a great challenge for orthopedic surgeons. The periosteum, which provides an essential blood supply and initial stem cells for bone tissue, plays an important role in the repair of bone defects. Reconstruction of the destroyed periosteum has attracted the attention of researchers exploring more satisfactory therapies to repair bone defects. However, periosteum-like biomaterials have yet to meet the clinical requirements and resolve this challenging problem. In this study, we manufactured a nanofiber artificial periosteum based on poly--caprolactone (PCL), in which tantalum nanoparticles (TaNPs) and nanoscale magnesium oxide (MgO) were introduced to enhance its osteogenic and angiogenic ability. The results of in vitro experiments indicate that the PCL/Ta/MgO artificial periosteum, with excellent cytocompatibility, can promote the proliferation of both bone marrow mesenchymal stem cells (BMSCs) and endothelial progenitor cells (EPCs). Furthermore, the incorporation of TaNPs and nano-MgO could synergistically enhance the osteogenic differentiation of BMSCs and the angiogenic properties of EPCs. Similarly, results of in vivo experiments from the subcutaneous implantation and critical-sized calvarial defect models showed that the PCL/Ta/MgO artificial periosteum combined the brilliant osteogenesis and angiogenesis abilities, promoting vascularized bone formation to repair critical-sized calvarial defects. Taken together, our study suggests that the strategy of stimulating repairing bone defects can be achieved with periosteum repaired in situ and the proposed artificial periosteum can act as a bioactive medium for accelerating bone healing.